KEMAMPUAN KOMUNIKASI PENYULUH DALAM PEMANFAATAN PEKARANGAN RUMAH DI KELURAHAN ANAWAI KECAMATAN WUA-WUA KOTA KENDARI - Nur Pausia Salsalbila; Sukmawati Abdullah; Yoenita Jayadisastra (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
The Indonesian context is characterized by significant agricultural potential, which necessitates the enhancement of human capital through the implementation of agricultural extension services. In Anawai Village, initiatives to leverage yards for food security have demonstrated favorable outcomes, though challenges to the efficacy of these efforts persist, including the communication competencies of extension workers and the limited engagement of certain farmers. The objective of this study is to ascertain the communication skills of extension workers regarding the utilization of home gardens in Anawai Village, Wua-Wua District, Kendari City. The population under study comprised 102 farmers from Anawai Village who utilize home gardens. The research sample was obtained through the application of the Slovin formula, with a margin of error set at 10%, thereby yielding a sample of 50 farmers. The simple random sampling technique was utilized in the research sampling. The present study employed a quantitative approach. The data for this study was collected through a combination of methods, including observation, in-depth interviews, and the administration of questionnaires. The research variable was the communication skills of extension workers in the utilization of home gardens. The collected data were then subjected to analysis using descriptive methods. The findings indicated that the communication skills exhibited by extension workers in Anawai Village were predominantly in the high category, with a percentage of 92% and 8% in the moderate category. The extension workers demonstrated a high level of verbal communication proficiency, with 88% exhibiting effective verbal expression and 90% demonstrating non-verbal communication skills through facial expressions, eye contact, and attitudes that facilitated discussion.